Beyond Food Distribution: The Context of Food Bank Innovation in Alabama. Issue 4 (3rd July 2020) - Strickland, Kathryn; Whitman, John R.
ABSTRACT: In Alabama, four food banks serve a population with the third highest rate of food insecurity in the U.S. All four food banks underperform according to a standard food distribution metric. Despite underperformance, three of the four have launched innovative social programs including an advocacy organization, revolving loan fund, local food hub, mother's milk bank, and a senior benefits enrollment center. The research question is: What environmental factors explain how these chronically underperforming food banks undertook innovations that expand the definition of a traditional food bank. This paper uses a conceptual framework of innovation-inducing environments to analyze the situations that led these food banks to innovate beyond food distribution. As hunger is a global challenge interrelated to other human needs, the findings may have implications for other under-resourced regions.